Cooperative Financial Performance: Business Efficiency and Members Efficiency: (Case Study of KUD Mandiri Bayongbong, Province of West Java) - Resti Pandini; Sugiyanto Sugiyanto (J-Coop : Journal of Co-operative, 2025)
KUD Mandiri Bayongbong operates in various business fields with very fluctuating business development, especially in terms of profitability over the last five years. This research aims to determine the factors of change in cooperative performance from the aspect of business efficiency as measured by Return On Equity (ROE) and member efficiency as measured by ROE' which is adjusted to the benefits received by members, using Du Pont System analysis. The research method used is quantitative descriptive, using secondary data from cooperative documentation supported by interviews. The research results show that changes in Business Efficiency are caused by changes in Net Profit Margin (NPM) and Return on Assets (ROA), ROA is influenced by changes in Total Asset Turn Over (TATO) and Equity Multiplier. The increase in Member Efficiency is also reflected in changes in NPM obtained from residual operating results (SHU) and economic benefits from services, as well as ROA.